Low for Long and Risk-Taking - Adrian, Tobias (Departmental Papers; Departmental Paper ;, 2020)
The COVID-19 pandemic is causing an unprecedented worldwide economic contraction, leading central banks to reduce interest rates to historically low levels and making unconventional monetary policies-including 'low for long' interest rates and asset purchases-increasingly common. Arguably, however, the policies implemented are efficient because they encourage increased risk-taking, and they may have, if unintentionally, increase medium- and long-run macro-financial vulnerabilities. This paper argues that the resulting trade-offs need to be carefully accounted for in monetary policy models and outlines how that can be achieved in practice.